Pengaruh Kesadara Wajib Pajaka, Sanksi Pajak Dan Oerigram Pemutihan Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di SAMSAT Manyar Surabaya - Aprianus Hendrikus Lando; Adiati Trihastuti (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to determine the effect of taxpayer awareness, tax sanctions, and tax write-off programs on motor vehicle taxpayer compliance at SAMSAT Manyar Surabaya. This study uses a type of quantitative research with the sampling technique used is accidental sampling. The sampling technique uses the slovin formula. The samples obtained amounted to 100 motorized vehicle taxpayers registered at SAMSAT Manyar Surabaya. Data collection was carried out by distributing questionnaires to motor vehicle taxpayers registered at SAMSAT Manyar Surabaya. Data were analyzed with descriptive statistical tests, classical assumption tests, and hypothesis testing with the help of the SPSS version 26 application.The results of this study indicate that taxpayer awareness does not have a positive effect on motor vehicle taxpayer compliance, tax sanctions do not have a positive effect on motor vehicle taxpayer compliance, and the tax bleaching program has an influence on motor vehicle taxpayer compliance at SAMSAT Manyar Surabaya.